2018
DOI: 10.3389/fneur.2018.00681
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Footprints Can Improve Walking Performance in People With Parkinson's Disease

Abstract: In Parkinson's disease (PD) self-directed movement, such as walking, is often found to be impaired while goal directed movement, such as catching a ball, stays relatively unaltered. This dichotomy is most clearly observed when sensory cueing techniques are used to deliver patterns of sound and/or light which in turn act as an external guide that improves gait performance. In this study we developed visual cues that could be presented in an immersive, interactive virtual reality (VR) environment. By controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Increasing the amount of external information provided to individuals with PD, such as through cueing, can significantly improve acquisition, automaticity, and retention of motor tasks, even once cues are removed (67, 120). The beneficial effects of cueing on gait and motor learning (121, 122) in PD are likely largely caused by addressing cognitive factors of the disease, such as attention (71). By directing attention to the motor action being practiced and giving feedback about its correctness, cueing can facilitate feedforward learning.…”
Section: Motor Learning In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the amount of external information provided to individuals with PD, such as through cueing, can significantly improve acquisition, automaticity, and retention of motor tasks, even once cues are removed (67, 120). The beneficial effects of cueing on gait and motor learning (121, 122) in PD are likely largely caused by addressing cognitive factors of the disease, such as attention (71). By directing attention to the motor action being practiced and giving feedback about its correctness, cueing can facilitate feedforward learning.…”
Section: Motor Learning In Pdmentioning
confidence: 99%
“…The use of technology in training of gait and balance for PD has been of interest. Several studies have utilized gamification of training, technology to assist, resist or create movements or perturbation, augmented feedback and VR (119, 121, 139, 144, 155, 169, 172, 173, 179, 180, 182, 183, 189). Cueing in particular shows promise and is an important area of research (120, 145, 155, 157162, 171, 173, 190).…”
Section: Effect Of Training On Pigdmentioning
confidence: 99%
“…One of the longest studied and most documented techniques for gait rehabilitation in PD is the use of sensory cueing (20, 21). Several studies have shown improvement in electromyographic and spatiotemporal parameters of gait in PD patients undergoing gait training with auditory, visual, and tactile cues (2227).…”
Section: Introductionmentioning
confidence: 99%
“…Motor impairments are observed when PD patients rely on internal control processes but have preserved externally cued performances ( 48 51 ). The use of external sensory cues as a strategy to facilitate movement continuity has been extensively documented in the locomotor activity domain using rhythmic auditory stimulation and visual stimulation ( 52 57 ). Dynamic visual cues are also involved in the visual perception of one owns actions ( 58 ) in terms of optic flow.…”
Section: Discussionmentioning
confidence: 99%